Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

See more answers at brainly.com

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions

We are removing 3

ie subtracting 3 each time

7 - 3 = 4
4 - 3 = 1
1 - 3 = -2

then -5, then -8 right?

in general, to get the next term f(n+1) you subtract 3 from the nth term
f(n+1) = f(n) - 3

yeah and it goes on forever

So it would be option C: f(1) = 7, f(n + 1) = f(n) - 4; for n ≥ 1

|dw:1436759995533:dw|

you'll do that for n = 2, n = 3, etc

I still think it's option C

no we aren't subtracting 4 each time

I don't get this at all then

Its A

that gives the term right after the nth term, the f(n+1) term
which is why
f(n+1) = f(n) - 3

look at f(n+1) = f(n) - 3
what happens when you replace every n with say n = 3

f(4)=f(3)-3?

All I did was substitute 'n' with 3

do you see how f(n) is the nth term?